Synthesis and Supramolecular Assemblies of Substituted Cycloparaphenylenes - Kohrs, Daniel; Justus Liebig University Giessen (My University, 2023)
Cycloparaphenylenes (CPPs) represent the shortest cutout of armchair single-walled carbon nanotubes (SWCNTs). These three-dimensional structures solely built from sp2-hybridized subunits contain a considerable amount of strain arising from this unusual arrangement. This needs to be built throughout the synthesis and requires a strategy, targeting on a strainreduced macrocycle prior to the formation of the CPP. One of these strategies which relies on a modular macrocyclization through palladium catalyzed Suzuki cross-coupling was combined with a [2+2+2] cycloaddition (CA) strategy to introduce tert-butyl (t-Bu) esters to the central building block. Thus, one [8] and two [10]CPP analogues equipped with t-Bu esters could be synthesized. The derivatives of [10]CPP were of particular interest as [10]CPP is, reasoned by its size, well suited to build inclusion complexes with the fullerenes C60 and C70. The influence of the substituents on the association behavior to these carbon allotropes was investigated and quantified by fluorescence-quenching experiments as well as computational chemistry to gain further insight into the experimental results. An interplay of multiple phenomena influenced the association, from which the increased dihedral angle, arising between the substituted and the neighboring phenyl rings, was attributed as the main contributor to decrease the association. Additional interactions emerging between the substituents and the fullerene were attenuating this effect and were differently strong for the two fullerenes. The achieved insights were compared to another functionalized [10]CPP analogue reported by the Wegner group. Further, malonyl ester derivatives of C60 with different alkyl chains were synthesized and used to investigate interactions occurring between the ester functionalities of the fullerene and t-Bu esters from one CPP derivative and were compared to results obtained for [10]CPP.
Keywords: ddc:500